2019
DOI: 10.1007/s00394-019-01976-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea catechins with caffeine on energy expenditure in middle-aged men and women: a randomized, double-blind, placebo-controlled, crossover trial

Abstract: Purpose It has been reported that tea catechins increase energy metabolism, but their effect on resting metabolic rate (RMR) remains under debate. This study aimed to examine the effect of repeated intake of tea catechins on energy metabolism in the resting state in middle-aged men and women. Methods A total of 30 middle-aged men and women [13 women; age (mean ± SD) 52 ± 4 years; BMI 21.9 ± 2.2 kg/m 2 ] were recruited. A randomized, double-blind, crossover study was conducted using a tea catechin-enriched beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A strength of this systematic review is the fact that the included studies considered green tea extracts or, at least, very small amounts of caffeine (<50 mg of the total content of green tea extract). Recent interesting studies have investigated the effects of green tea extract supplementation on metabolic parameters and body composition, but these supplement had high caffeine contents [ 69 , 70 , 71 ]. The same observation was first carried out by Dullo et al, who revealed that the effects of the green tea extract in enhancing thermogenesis and fat oxidation could not solely be explained on the basis of its caffeine content, because treatment with an amount of caffeine equivalent to that in the extract failed to alter EE, RQ, or substrate oxidation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this systematic review is the fact that the included studies considered green tea extracts or, at least, very small amounts of caffeine (<50 mg of the total content of green tea extract). Recent interesting studies have investigated the effects of green tea extract supplementation on metabolic parameters and body composition, but these supplement had high caffeine contents [ 69 , 70 , 71 ]. The same observation was first carried out by Dullo et al, who revealed that the effects of the green tea extract in enhancing thermogenesis and fat oxidation could not solely be explained on the basis of its caffeine content, because treatment with an amount of caffeine equivalent to that in the extract failed to alter EE, RQ, or substrate oxidation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists took baseline measurements, measured fasting, resting metabolic rate (RMR) and EE after the 2-week ingestion of test beverage, and simultaneously measured forehead temperature (a proxy for core temperature) and skin temperature. Results indicated that EE increased significantly after ingestion of the tea catechin beverage compared with the placebo beverage [132]. Katada et al concluded that ingestion of tea catechin along with caffeine for 2 weeks increases thermogenesis and EE immediately after ingestion of the test beverage.…”
Section: Catechins In Obesity: Human Studiesmentioning
confidence: 99%
“…However, other studies that used randomized controlled trial (RCT) designs did yield similar results. A single-blind, RCT conducted in individuals with obesity found a significant decrease in body weight and waist circumference over 8 weeks of supplementation with a green tea beverage that contained EGCG and caffeine as compared to a placebo beverage [132].…”
Section: Catechins In Obesity: Human Studiesmentioning
confidence: 99%
“… 8 Recently, Caffeine was demonstrated to enhance the physical activity-driven caloric cost in rats. 9 Recently Katada et al 10 reported that a 2-week consumption of catechins with caffeine markedly increased the energy expenditure in middle-aged human subjects. Use of such thermogenic agents is a promising strategy to mitigate obesity and associated metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%